(untitled) (Medicine Today, 2017)
Abdominal tuberculosis constitute up to 12% of extrapulmonary TB and is sixth frequent site of extrapulmonary involvement. The most common sites of involvement is the ileocaecalregion. Other site of involvement in descending order are ascending colon jejunum, appendix, duodenum, stomach, esophagus, sigmoid colon and rectum. Abdominal TB has diagnostic dilemma due to its diverse and non-specific clinical presentation and has no single most specific, sensitive diagnostic test. A high index of suspicion, common and rare clinical feature, adequate imaging study, endoscopy, enteroscopy, laparoscopy, laparotomy, biopsy with histopathology, Mycobacterial isolation, Quantiferon-TB Gold, GeneXpert Assay, MULTIPLEX PCR and clinical response to anti TB therapy are considered for early diagnosis to reduce morbidity and mortality. Six month antiTB regime is effective as nine or 12month therapy. MDR TB and frequent interruption of therapy should considered in nonresponder to standard therapy. Surgery is required for minority cases that developed complications not responding to medical therpy. Medicine Today 2016 Vol.28(1): 39-45